How Do Nepotism and Favouritism Affect Organisational Climate? - Vveinhardt, Jolita; Bendaraviciene, Rita (Frontiers in Psychology, 2022)
This study seeks to determine the effect of nepotism and favouritism on organisational climate. Using the method of random sampling, 269 persons working in Lithuanian organisations were surveyed. The received data was analysed via the application of the methods of correlation and linear regression. It was determined that organisational climate is influenced significantly by such variables as the manager’s behaviour, safety and relationships with employees, values and traditions, communication, sharing of information, behaviour of employees, and inter-relationships and tolerance of one another. Meanwhile, nepotism and favouritism are influenced by the lower number of climate variables (fear related to the absence of concreteness and security; joining an organisation, union and tolerance of individuals who have shared interests). This study fills the void in the knowledge of connections that nepotism and favouritism have with organisational climate, drawing attention to the mutual interaction between these phenomena. The article presents a discussion and the research limitations and provides guidelines for further research.